The level of the autoantibodies to antigenes of the thyroid gland at metabolic syndrome with deficiency of estrogens and the hypothyroidism - V. V. Kozak (Zaporozhye State Medical University, 2012)
It has been shown that the concentration of autoantibodies to thyroperoxidase was significantly increased in rats with estrogen-deficiency. The combination of hypoestrogenia and metabolic syndrome with hypothyroidism intensified destructive processes in the thyroid gland. 17β-estradiol had the protective effect to the damaged thyroid gland in ovarioectomized animals with metabolic syndrome and hypothyroidism that was confirmed by significant reduction of concentration of autoantibodies to thyroperoxidase.